Concepções e perspectivas de agência epistêmica - Santin, Thiago Rafael (2015)
This thesis inquires about the term “epistemic agency”, exploring different conceptions and assessing perspectives about its use and meaning. It is divided in three chapters. In the first chapter, it brings considerations about the term “agency”, its origin and multiplicity of uses. It also exposes the term’s emergence on epistemology, and a brief historical characterization. Additionally, it sets epistemic deontologism on the ethics of belief discussion, constructing the emergence of doxastic epistemic agency, and it shows the problem of doxastic involuntarism and some responses to the problem. At the end, presents our proposal, with a skeptical conclusion. In the second chapter, it examines reflective agency, as well as presents virtue epistemology and performance metaphysics. It also defines epistemic agency throughout reflective performances and shows three critics and a proposal considering the critics, again concluding skeptically. In the third chapter, leaves normativity behind and approaches ameliorative epistemology. It makes an argumentative reconstruction of empirical research considerations diagnosing human actual cognitive capacities, and inquires possibilities of improving their systematic failures or cognitive biases. It concludes skeptically about the possibility of improvement relying on individuals and indicates the possibility of collective restrictions on individuals called epistemic paternalism. In addition, it presents social epistemology and epistemic paternalism, and finally, concludes indicating skepticism about individual epistemic agency, on one side, and the possibility of collective epistemic agency, on the other.